Penyidikan Terhadap Kelalaian Yang Mengakibatkan Kematian Oleh Pengendara Di Jalan Raya (Studi Kasus Lakalantas Polrestabes Makassar) - Ilham Ashari; Askari Razak; Nur Fadhila Mappaselleng (Qawanin Jurnal Ilmu Hukum, 2020)
This research was conducted to determine how the investigation of the Makassar Police Traffic Police, in carrying out investigations into negligence that resulted in the death of motorists on the highway, and what are the factors that affect the course of the investigation process carried out by the Makassar Police Traffic Police.Based on the results of research conducted in empirically analyzing the investigation process and the factors that can influence it, it can be concluded that the investigation of negligence that results in death on the road is that the driver's behavior in driving his vehicle has been negligent or careless which results in death, in this case. is a criminal act that can be subject to criminal penalties for the rider. The Makassar Police District Police handled the case by processing motorists who due to their negligence resulted in death by carrying out investigations and investigations where the process was to find out whether the rider fulfilled the elements and could be made a suspect so that the event could be made to delegate the case to the prosecutor for further processing. .The investigation process can be influenced by the absence of eye witnesses at the scene of the case, which complicates the course of the investigation process and the lack of public awareness to report when they find out about a crime that has occurred on the road because they consider it an important act. Investigation; Negligence; Accidentally Resulting in Death; Driver; On the highway;